The inverse association between serum anti-streptolysin-O titers and the frequency of exacerbations of in childhood - (:unkn) unknown (My University, 2000)
Background: the decline in infections in childhood may contribute to the rising severity and prevalence of atopic disorders in developed countries. Support for this hypotnesis has been obtained from findings of an inverse association between tuberculin responses and atopy ana from findings of high prevalence of asthma in certain islands with low prevalence of respiratory infections. With this regard, we investigated the association between serum antistreptolysin-O (ASO) titers and the frequency of exacerbations of asthma in childhood. Methods: thirty atopic asthmatic children who has no sign of upper respiratory tract infection at the time of presentation or during the previous two months were included in the study. Serum ASO titer was measured as an indicator of past streptococcal upper respiratory tract infections. ASO titer > or = 200 Todd units was accepted as positive. Results: a statistically significant association is found between high anti-streptolysin-O titers and decreased number of exacerbations in those children. Conclusions: our data suggests that streptococcal infections might be a factor attenuating asthma in cnildhood.
Keywords: ASO; Asthma; Children